An Overview on Nature Inspired Planar Broadband Antennas - Patre S.R.; Singh S.P. (My University, 2025)
This paper presents an overview on planar broadband antennas whose radiator has nature-inspired geometry. The natural leaves and flower petals have curved boundaries and multiple segments. These features of nature-inspired geometries are advantageous to get closely spaced multiple resonances hence broadband characteristics when arranged in specific antenna configuration and optimized properly. A case study on recently developed flower- and leaf-shaped planar monopole antennas for broad frequency range is given in this paper. In addition, some of the nature-inspired antennas are analyzed through surface current distribution which helps to understand the fundamental relation of operating frequency and active element of antenna. © 2023 IEEE.